Pengaruh Lagu “Diri” Karya Tulus Di Youtube Terhadap Sikap Self Compassion Pada Persatuan Orang Tua Dengan Anak Down Syndrome Jawa Tengah Dan Jawa Barat - Prasetyo, Christabel Betsy Benita Rachel; Lubis, Fardiah Oktariani; Kusumaningrum, Rastri (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to explain the influence of the brand ambassador "Raffi Ahmad" and brand image on the intention to buy the Erigo brand either partially or simultaneously with a descriptive and quantitative approach. The number of samples is 106 respondents using purposive sampling technique. Furthermore, the data was analyzed by path analysis (path analysis). The results showed that the correlation between brand ambassador and brand image had a correlation value of 0.767 with a significance of 0.000. meaning that the brand ambassador "Raffi Ahmad" with brand image has a strong correlation. Partially, buying interest has a sig value (0.000) <(0.05) and tcount (5.621)> ttable (1.659) so it is Hodirejected. This means that the brand ambassador "Raffi Ahmad" partially has a significant effect on buying interest. Brand image on purchase intention has a sig value (0.000) <(0.05) and tcount (5.130) > ttable (1.659) so Ho is rejected. This means that brand image partially has a significant effect on purchase intention. Simultaneously the brand ambassador "Raffi Ahmad" and brand image on buying interest have a value of sig (0.000) <(0.05) and Fcount (124.032)>Ftable (3.08) then Ho is rejected. Thus it can be concluded that the brand ambassador "Raffi Ahmad" and brand image simultaneously influence purchase intention.